Diseño de la red de agua potable, alcantarillado sanitario - pluvial y depuración de aguas negras, del sector la Rosita 2, cantón Pasaje, provincia de El Oro. - Murillo Lalangui, Carlos Ramón (2015)
Inadequate provision of potable water and the lack of a sewage system - rain in the La Rosita 2 is the main problem that generates very high consequences for health and good living of people and contributing to pollution environmental this generates in this part of Canton Pasaje, El Oro province. That is why a project that aims primarily to design a network of potable water, sanitary sewer is proposed - Stormwater and Sewage purification Sector "La Rosita 2", Canton Pasaje, El Oro province. The research was performed to meet the project was based on the literature inquiry both the website and in the documentation available at the university library, in addition to practical and descriptive mode while maintaining constant contact with the sector under study. The results of the survey, topography, soil analysis and in addition to the help of health standards, were used for the proper development of the design of the health network and a treatment plant wastewater to allow us to solve much of the environmental pollution caused by discharges of waters "No-Treated". Finally, this project is very necessary and was reviewed and approved by specialist engineers in the health area, it only remains to continue the construction of the work, which will be available to any institution that has the financial capacity to execute in the first instance figure GAD City of Canton Pasaje.